2019
DOI: 10.1038/s41598-019-45987-2
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of metals in calanoid copepods by oral intake

Abstract: We demonstrated that oral intake of water by two calanoid copepods, Pseudodiaptomus annandalei and Eurytemora affinis takes place and has implications for their ecotoxicology. In the first experiment, copepods were exposed to a dyed medium, which allowed us to visually examine the possibility of water uptake by the copepod. We observed that both copepod species were taking in water orally and evacuated dye at different speeds. This exposure left concentrated dye in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A significantly higher (p<0.05) concentration of heavy metals in Juru waters, copepods and sediments compared to those in Gula estuary might be attributed to industrialization and urbanization along the Juru coastal area. Wang and Fisher (1998) and Kadiene et al (2019) found that copepods can completely assimilate ingested trace elements Metal concentrations in estuarine waters fluct -1 Fig. 3 Comparison of Cd, Cu, Pb, and Zn concentrations (μg g ) in sediment throughout the study period in Juru and Gula estuaries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significantly higher (p<0.05) concentration of heavy metals in Juru waters, copepods and sediments compared to those in Gula estuary might be attributed to industrialization and urbanization along the Juru coastal area. Wang and Fisher (1998) and Kadiene et al (2019) found that copepods can completely assimilate ingested trace elements Metal concentrations in estuarine waters fluct -1 Fig. 3 Comparison of Cd, Cu, Pb, and Zn concentrations (μg g ) in sediment throughout the study period in Juru and Gula estuaries.…”
Section: Resultsmentioning
confidence: 99%
“…The nMDS showed distinct separation of two study sites in terms of metals contents in copepods and sediments, indicating that high metal contents in sediments would be available to copepods and would ffect the health of marine food chain. Fang et al (2006) and Kadiene et al (2019) reported that copepods have high capacity of accumulating and bioconcentrating trace metals and can be used as an effective biological indicator for assessing and monitoring metal contamination in marine environment. In addition, Wang and Fisher (1998) also noted higher fraction of metals found in copepods' soft tissues compared to those obtained from water indicating higher uptake rate of metals through ingestion oted that heavy metals were highly persistent in sediment and biological compartments, such as copepods, making them suitable markers for environmental health monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that copepods create feeding currents and selectively ingest food particles [ 87 , 88 , 89 ]. Kadiene et al [ 20 ] demonstrated that metal uptake in copepods from the dissolved phase was significantly higher than metals from their diet.…”
Section: Discussionmentioning
confidence: 99%
“…One of the overarching effects of OA on phytoplankton communities is that phytoplankton will likely alter the chemical speciation of trace metals [ 4 , 17 , 18 , 19 , 20 ]. Phytoplankton concentrate metals and transuranic elements from surrounding waters [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…They provide essential ecosystem services by supporting the maintenance of fish of economic importance. They are thus suitable model organisms for ecotoxicology and genomics studies [2,4,5] due to their primordial position in the trophic chain, copepod ubiquity, diversity, and capacity to transfer pollutants to higher trophic levels [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%